Analisis Canvas Strategi Mengenai Produk dan Srategi Pemasaran Produk Pada BMT Dana Mentari - Sari, Sinta Kartika; Putri, Dina Alliah Anggreani; Shafrani, Yoiz Shofwa (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study intends to investigate the business model and product marketing strategy of BMT Dana Mentari Muhammadiyah Purwokerto using the Business Model Canvas (BMC) approach. The background of this research is rooted in the need for Islamic microfinance institutions to adapt amidst increasing competition, particularly in product development and marketing. The research uses a descriptive qualitative approach, with data collected through in-depth interviews with BMT management. The findings suggest that BMT Dana Mentari has implemented the nine elements of the BMC comprehensively, including community-based customer segmentation, strong Sharia-compliant value propositions, and marketing strategies such as direct outreach and personal selling. However, challenges remain, particularly in service digitalization and promotional efforts. The implications of this study highlight the importance of continuous innovation in Sharia-based products and marketing strategies to enhance competitiveness and institutional sustainability.